Effect of Lactobacillus plantarum fermented barley on plasma glycolipids and insulin sensitivity in subjects with metabolic syndrome. Issue 11 (27th September 2020) - Pan, Ruirong; Xu, Tian; Bai, Juan; Xia, Song; Liu, Qiang; Li, Jie; Xiao, Xiang; Dong, Ying
Abstract: Fermented barley (FB) flour by Lactobacillus plantarum is richer in dietary fiber, polyphenols, gamma‐aminobutyric acid, and other biologically active ingredients. This study aimed to determine the impacts of fermented barley ‐ wheat flour compound noodle (FBWN) on glucose and fat metabolism in subjects with metabolic syndrome. This was a single‐blinded and parallel 10‐week clinical trial study. Subjects were randomly assigned into the trial group (FBWN) and whole wheat noodles group (WWN), and were measured on the beginning of week 3 and the ending of week 10. The glucose level at 30 and 60 min was significantly decreased after FBWN intervention. Levels of fasting blood glucose, HbA1c, and TG were all declined after FBWN intervention compared to before in the trial group. Moreover, the fat mass, fat rate, and visceral fat were decreased by 6.48, 7.19, 6.3 kg after FBWN intervention, respectively, while muscle mass and basal metabolic rate rose 7.44 kg and 252.60 kcal. Practical applications: Many studies have illustrated that the extraction of fermented barley held the activities of anti‐obesity, antitumor, and so on. Moreover, this present study evaluated the effects of fermented barley by Lactobacillus plantarum on patients with metabolic syndrome. Results indicated that FB benefits the subjects on improving plasma glycolipids and insulin sensitivity, decreasing visceral fat level, and increasing satiety. The findings showed that the products of FB may be beneficial to dietary manipulations, thus, reducing the burden of patients. Abstract : The glucose level with MS was decreased after FBWN intervention. Levels of fasting blood glucose, HbA1c, and TG were all declined after FBWN intervention. The fat mass, fat rate, and visceral fat were decreased while muscle mass and basal metabolic rose.